Reconceptualizing and Managing Reputation Risk in the Knowledge Economy: Toward Reputable Action - Scott, Susan V.; Walsham, Geoff (Organization Science, 2005)
Globalizing knowledge economies foster conditions that intensify the role and value of organizational reputation risk. In an enterprise-focused era, reputation is a key strategic construct that can act as a boundary object linking communities within and between organizations. Yet approaches to its management tend to be reactive and remain under the hold of industrial society principles. Definitions of reputation risk in the existing literature and the business community have a tendency to be static and asset oriented. We suggest that this contrasts sharply with insights on the social construction of knowledge that inform recent risk studies. Drawing on this critique, we argue that the ambivalence engendered by on-going processes of definition (responsibilities, boundaries, fact construction) characterizing the knowledge society demands a reconceptualization of reputation risk. We propose a reconceptualization of reputation risk that not only incorporates a more sophisticated view of reputation, but also acknowledges the role that risk and trust relations can play in its constitution. In addition to contributing to the theoretical development of reputation risk in the organization studies literature, we develop the notion of reputable action as a guiding principle for realizing active trust development in the practical management of reputation risk.